Rasionalitas Penggunaan Obat Pada Kasus Diare Pasien Balita di RSU PKU Muhammadiyah Gombong Periode Juli-Desember 2017 - astuti, dyah puji (WARTA BHAKTI HUSADA MULIA : Jurnal Kesehatan, 2018)
Diarrhea is a cause of morbidity and mortality in Indonesia, especially in infants. PKU Muhammadiyah Gombong Hospital is a health facility in the Kebumen area and has enough care for diarrhea patients. Medical record data for 3 months (October-December 2017 period) 44 diarrhea patients were hospitalized. The purpose of this study was to determine the rationality of drug use in the treatment of diarrhea in underfive patients and the percentage of drug administration from existing cases and what types of drugs were given to toddlers in the inpatient care of PKU Muhammadiyah Gombong Hospital. The method of this research is non-experimental research with retrospective data collection where samples are determined by purposive sampling method. The results showed that the largest percentage of diarrheal patients was experienced in infants aged 0 - 1 as many as 48 (71.6%) where toddlers with male sex were more (41 toddlers) than female gender. The most common symptoms of diarrhea experienced by patients were fever, nausea and vomiting of 44.8%. The administration of zinc supplements in diarrhea patients was 15 patients (22.40%). Diagnosis of diarrhea in patients at PKU Muhammadiyah Gombong Hospital, categorized as fulfilling the exact criteria indicated in this study as many as 67 gifts with a percentage of 100%, which is based on complaints experienced by patients. Proper administration of the drug amounts to 9 cases. Â 